The effect of Home-Based Supervised Ota-go Exercises on Quality of Life, Psychological Well-Being, and Social Isolation Among Older Adults: A Quasi- Experimental Study - Mohsen Sahranavard; Rasool Norouzi Seyed Hossini; Marjan Saffari; Pouya Farokhnezhad Afshar (Iranian South Medical Journal)
Background: Physical activity can slow body deterioration, enhance quality of life, and improve psychological well-being in older adults. The present study aimed to determine the effects of home-based supervised Otago exercises on the quality of life, psychological well-being, and social isolation of older adults in Bushehr city. Materials and Methods: This quasi-experimental study involved 30 older adults (> 60 years old) who volunteered to take part and were randomly divided into an experimental and a control group. The experimental group performed Otago exercises three 45-min sessions per week for 8 weeks. During this period, the control group maintained their normal lives. The World Health Organization quality of life questionnaire, the Lubben Social Network, and the Ryff Psychological Well-being Questionnaire were used to assess quality of life, social isolation, and psychological well-being. The analysis of the covariance test was utilized for statistical analysis. Results: The results of statistical analysis after the exercise intervention indicated a significant improvement in quality of life and its subscales (P<0.05), psychological well-being and its subscales (P<0.05), and an increase in social networks with friends and family (P<0.05) in the Otago group compared to the control. Conclusion: According to our study, supervised Otago exercises at home have a positive impact on increasing quality of life and social support, while reducing psychological problems. Given the limitations facing older adults in performing physical activities outside home, it is recommended that this exercise method be utilized to enhance quality of life, psychological well-being, and reduce social isolation.